Combating environmental pollution crimes through environmental tax instruments in Indonesian development law - Viski Umar Hajir Nasution (Priviet Social Sciences Journal, 2025)
Environmental pollution remains a critical issue in Indonesia’s development process, as rapid industrialization and economic growth often lead to significant environmental degradation. The inadequacy of conventional legal enforcement mechanisms, which primarily rely on administrative and criminal sanctions, has failed to create a deterrent effect on environmental offenders. This study examines the role of environmental tax instruments as alternative legal and economic tools to prevent and combat environmental pollution crimes within the framework of Indonesian development law. Using a normative juridical (doctrinal) approach that is prescriptive and analytical in nature, this study analyzes relevant legislation, legal doctrines, and the conceptual foundations of environmental and tax law. The methods applied include a statute, conceptual, and case approach, supported by qualitative analysis through grammatical, systematic, and historical interpretation. The findings indicate that environmental taxes serve not only as a fiscal instrument but also as a preventive legal mechanism that embodies the polluter pays principle, promoting compliance and environmental accountability among economic actors. Strengthening the legal framework and policy implementation of environmental taxes is essential for achieving sustainable development goals and ensuring environmental justice in Indonesia.